PROSES NEGOSIASI PARTAI ACEH DAN UPAYA PENERIMAAN PILKADA ACEH TAHUN 2012 - Sudirman, Sudirman; Lubis, Sahruddin; Rambe, Safrizal (Program Studi Sosiologi Universitas Malikussaleh, 2023)
This study examines the negotiation process of the Acehnese parties and their acceptance efforts in the 2012 regional elections. The study of the political efforts in negotiating carried out by the Aceh Party elite is not only limited to voicing through political demonstrations, but also taking legal steps through lawsuits against The Constitutional Court is one step in political negotiations with the central government to continue its power and support the creation of sustainable peace in Aceh. This study uses the perspective of negotiation theory and effective political communication. The data collection method used in this research was through an observation approach, document study and in-depth interviews with; Aceh Party elite, Chairman of the Independent Election Commission (KIP), Civil Society and academics. Finally, this study concluded that. First, the refusal to register is part of the negotiation process between the Aceh Party and the central government as a form of commitment to the mandate of the Helsinki MoU and the mandate of the Republic of Indonesia Government Law (UUPA) Number 6 of 2006 concerning the Aceh Government and the sustainability of peace. Second, the Aceh Party formed the Free Aceh Political and Ideological Framing Alliance. This political alliance can help strengthen the voter base, expand campaign reach and strengthen political influence. Third, building effective communication with supporting parties to mobilize support for the Aceh Party.Studi ini mengkaji tentang proses negosiasi partai Aceh dan upaya penerimaan dalam Pilkada tahun 2012. Studi tentang upaya-upaya politik dalam bernegosiasi yang dilakukan oleh elit Partai Aceh bukan hanya sebatas menyuarakan lewat aksi politik unjuk rasa, namun juga mengambil langkah-langkah hukum melalui gugatan ke Mahkamah Konstitusi merupakan salah satu langkah negosiasi politik dengan pemerintah pusat untuk melanjutkan kekuasaaan dan mendukung terciptanya perdamaian berkelanjutan di Aceh. Studi ini menggunakan perspektif teori negosiasi dan komunikasi politik efektif. Metode pengumpulan data yang dilakukan dalam penelitian ini melalui pendekatan observasi, studi dokumen dan wawancara mendalam dengan; elit Partai Aceh, Ketua Komisi Independen Pemilihan (KIP), Masyarakat Sipil dan akademisi. Akhirnya, studi ini menyimpulkan bahwa. Pertama, penolakan pendaftaran merupakan bagian dari proses negosiasi Partai Aceh dan pemerintah pusat sebagai bentuk komitmen amanah Mou Helsinki dan amanah Undang-Undang Pemerintah Repuplik Indonesia (UUPA) Nomor 6 Tahun 2006 Tentang Pemerintah Aceh dan keberlajutan Perdamaian. Kedua, Partai Aceh membentuk Aliansi Politik dan Framing Idiologi Aceh Merdeka, aliansi politik ini dapat membantu memperkuat basis pemilih, memperluas jangkauan kampanye, dan memperkuat pengaruh politik. Ketiga, membangun komunikasi efektif dengan partai pendukung sebagai penggalangan dukungan Partai Aceh.